Model of Management Capacity Building for Improving The Quality of School - Djaman Satori; Aan Komariah (Intelektual Pustaka Media Utama, 2015)
This study was aimed to develop a Model of Management Capacity Building for Improving The Quality of Elementary School in Bandung, West Java. The research method used the research and development prosedure and the main stages were: a preliminary study, development of the design and the product model, expert analysis judgment, operational testing, validation testing through pre-experiment, and product dissemination. The model developed consisted of six components, i.e. vision, skills, resoures, insentive, action plan, and partnership. The study revealed that this model had a significant influence on improving the quality of education through capacity building school management in an integrative model of partnership between school, university and ministry of education.